The Shark in the Vitrine: Experiencing our Practice From the Inside Out With Transdisciplinary Lenses. (October 2014) - Samaras, Anastasia P.; Karczmarczyk, Diana; Smith, Lesley; Woodville, Louisa; Harmon, Laurie; Nasser, Ilham; Parsons, Seth A.; Smith, Toni M.; Borne, Kirk; Constantine, Lynne Scott; Mendoza, Esperanza Roman; Suh, Jennifer; et al.
The Scholars of Studying Teaching Collaborative engaged a dozen faculty members from 12 specializations and 4 colleges at a large public university in a 2-year teaching and research project with the goal of learning about and enacting a self-study of professional practice. Participants were selected from various disciplines to provoke alternative perspectives in whole group and critical friend teams. While we each conducted a self-study, we also designed and enacted a meta-study to assess our professional development within the context of the collaborative. We analyze the potential of engaging in collective self-study and report how the methodological challenges initiated transformational learning that bridged theory and praxis. Learning the self-study methodology was complex, but such concentration multiplied the impact of both personal and professional transformation. The study benefits faculty from a broad range of disciplines, at diverse stages in their academic careers, and working at every level of the academic hierarchy.